Urgensi Keterlibatan Orang Tua Dalam Mewujudkan Profil Pelajar Pancasila Di SMPN 1 Sumberrejo - Meilinda Nikmatut Taqiya; Khoirotus Silfiyah; Usman Roin; M. Jauharul Ma'arif (STIKes Ibnu Sina Ajibarang, 2023)
Parental involvement is very important in realizing the Pancasila student profile. However, now parents hand over all responsibility to the school in shaping children's behavior or character in accordance with Pancasila values. This research aims to determine the urgency and efforts of schools in realizing the Pancasila student profile in parental involvement. This research uses a descriptive qualitative approach with data collection techniques through observation and interviews. The research results show that there are four parent involvement activity programs in realizing the Pancasila student profile. (1) forming a parents' association (2) holding parents' classes; (3) holding inspiration classes; (4) holding a farewell art performance 9.